Honamli Goats Breed in South of Turkey I- Serum Mineral Analysis - Ayşe Özge Demir; Kıvanç Irak; Handan Mert; Nihat Mert; Nesrullah Ayşin; Inci Sogutlu (Turkish Journal of Agriculture: Food Science and Technology)
The objectivity of this study was to investigate some blood minerals and parameters in Honamli goats reared under semi-intensive conditions. 90 goats (2-4 ages) in different three herds kept under similar manage mental conditions were chosen as research materials in Teke Border of Antalya Province. Serum Ca 6.786±0.206 mg/dL, P 4.094±0.173 mg/dL, Cl 111.105±0.582 mmol/L, K 4.519±0.066 mmol/L, Mg 2.161±0.05 mg/dL, Na 148.047±0.508 mmol/L, Fe 110.706±2.510 μg/dL, UIBC 155.025±4.333 μg/dL and Tp 7.055±0.120 g/dL were determined by Roche Diagnostics, Cobas 8000 modular analyser series, immunoassay. After then, total iron- binding capacity (TIBC), transferrin (Tf), transferrin saturation (TSAT) and Ca++ levels were calculated from each other using different biochemical formulas. Ratios between the some minerals were calculated and presented in the text. Also, very high significant differences (P